2017
DOI: 10.18203/2320-6012.ijrms20174551
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, hematological, and laboratory presentation of acute lymphoblastic leukemia of children in Diyala province/Eastern Iraq

Abstract: Background: To show the initial presenting features the children of acute lymphoblastic leukemia presented till the diagnosis at oncology Center/ Diyala/ Iraq.Methods: A retrospective study, carried out during 2016-2017. The data include constitutional, hematological, and infiltrative features with laboratory findings registered at patient’s files until the diagnosis. Data were analyzed by Statistical Package of Social Sciences v. 20.Results: The total patients were 55, distributed into: T- cell (10.9%) and B-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
6
1
1
Order By: Relevance
“…A retrospective Iraqi study reported the initial presenting features of childhood leukemia were fever (81.8%), pallor (67.3%), hepatosplenomegaly (56.4%), lymphadenopathy (49.1%), bone pain (40%), anorexia (36.4%), and mucocutaneous bleeding (27.3%). (36) Reports vary on the relationship of residence with childhood leukemia. Our study showed that residence was not a risk factor for childhood leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective Iraqi study reported the initial presenting features of childhood leukemia were fever (81.8%), pallor (67.3%), hepatosplenomegaly (56.4%), lymphadenopathy (49.1%), bone pain (40%), anorexia (36.4%), and mucocutaneous bleeding (27.3%). (36) Reports vary on the relationship of residence with childhood leukemia. Our study showed that residence was not a risk factor for childhood leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly found in Eastern Iraq and India, where the most dominant type was L2, followed by L1 and L3. 12,18 The limitation of this study was inaccessible medical record data or incomplete data which caused data to be excluded, resulting in a lower sample population.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with findings from previous studies that fever, pallor, and hepatosplenomegaly are the main presenting complaints of ALL. 12,13 In addition to their infiltration to bone marrow, leukemic cells also infiltrate other organs. Spleen, liver, and lymph nodes are the most common infiltrated organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In developed countries, leukemia accounts for 30% of all cancers among children below 15 years of age, and is considered the most common childhood malignancy, where acute lymphoblastic leukemia (ALL) is the most predominant type representing 80% of all cases of leukemia. [1,2] Despite being a global public health problem, in developing countries the image of leukemia in children is different from that in developed countries, where its incidence is increasing with variations in survival rates and in methods and time of diagnosis. Genetic and environmental risk factors and differences in diagnosis and treatment may play major role in this variation.…”
Section: Introductionmentioning
confidence: 99%